Autonomous Aquaculture Farming System - Jong, Yi Sheng; Mohd Hezri Bin Mokhtar; Huda Bin A Majid (Progress in Engineering Application and Technology, 2021)
Aquaculture industry has been developed rapidly in recent decades. Farmers need to monitor the conditions in the breeding tank 24/7 to ensure everything works well. This is a serious inconvenience and financial affect to the owner of the farm. Thus, an autonomous breeding system for aquaculture is built to help to solve the problems faced by the farmers. A cost-efficient autonomous farming system is built to combine with the present aquaculture technology and knowledge in order to increase the productivity of the industry. The main purpose of this project is to study more on the proper habitat for the freshwater prawn or Macrobrachium Rosenbergii, develop a fully functional autonomous farming system which can provide a good living habitat for freshwater prawn farming and equip the autonomous system for prawn farming system with auto detection function to improve the success rate of the freshwater prawn for harvesting. Autonomous breeding system can improve the job efficiency of the farmers and upgrade the whole industry in terms of technology to a new era.